On the Impact of the Intermetallic Fe2Nb Laves Phase on the Mechanical Properties of Fe-6 Al-1.25 Nb-X W/Mo Fully Ferritic Light-Weight Steels - Robin Emmrich; Ulrich Krupp (Metals, 2021)
The present study aims at the development of precipitation hardening fully ferritic steels with increased aluminum and niobium content for application at elevated temperatures. The first and second material batch were alloyed with tungsten or molybdenum, respectively. To analyze the influence of these elements on the thermally induced precipitation of the intermetallic Fe2Nb Laves phase and thus on the mechanical properties, aging treatments with varying temperature and holding time are performed followed by X-ray diffraction (XRD) analysis and scanning electron microscopy (SEM) including elemental contrast based particle analysis as well as hardness measurements and tensile tests at room temperature and at 500 °C. The incorporation of molybdenum into the Laves phase sets in at an earlier stage of aging than the incorporation of tungsten, which leads to faster growth and coarsening of the Laves phase in the molybdenum-alloyed steel. Nevertheless, both concepts show a fast and massive increase in hardness (280 HV10) due to precipitation of Laves phase during aging at 650 °C. After 4 h aging, the yield strength increase at room temperature is 100 MPa, which stays stable at operation temperatures up to 500 °C.